Disturbed relationship between glucocorticoid receptor and 5-HT1AR/5-HT2AR in ADHD rats: A correlation study - Lin, Xiaoxia; Huang, Liang; Huang, Huifang; Ke, Zhongling; Chen, Yanhui (Frontiers in Neuroscience, 2023)
Objective This work is to investigate the alterations of the central 5-hydroxytryptamine (5-HT) system in spontaneously hypertensive rats (SHR) and the correlation with the behaviors of SHR, and to explore the effects of glucocorticoid intervention on the central 5-HT system and SHR behaviors. Materials and methods Three weeks old SHR were chosen as the attention-deficit hyperactivity disorder (ADHD) model and treated with glucocorticoid receptor (GR) agonist or inhibitor, whereas Wista Kyoto rats (WKY) were chosen as the normal control group. Open-field test and Làt maze test were used to evaluate the spontaneous activities and non-selective attention. The levels of 5-HT in the extracellular fluid specimens of the prefrontal cortex of rats were analyzed by high-performance liquid chromatography. The expressions of GR, 5-HT1A receptor (5-HT1AR), and 5-HT2A receptor (5-HT2AR) in the prefrontal cortex were analyzed through immunohistochemistry. Results Our study demonstrated that the 5-HT level was lower in the prefrontal cortex of SHR compared to that of WKY. The Open-field test and Làt maze test showed that GR agonist (dexamethasone, DEX) intervention ameliorated attention deficit and hyperactive behavior, whereas GR inhibitor (RU486) aggravated the disorders. With DEX, the expression levels of 5-HT and 5-HT2AR in the prefrontal cortex of SHR were significantly higher than those in the control group, whereas the expression level of 5-HT1AR was lower. However, the expression levels of 5-HT and 5-HT2AR were significantly decreased after the intervention with RU486, while the expression level of 5-HT1AR increased. Results showed that glucocorticoid was negatively correlated with 5-HT1AR and positively correlated with 5-HT2AR. Conclusion In the prefrontal cortex of ADHD rats, the down-regulation of 5-HT and 5-HT2AR expressions and the up-regulation of 5-HT1AR, compared with WYK rats, suggested a dysfunctional central 5-HT system in ADHD rats. The GR agonist can upregulate the expression of 5-HT and 5-HT2AR and downregulate the expression of 5-HT1AR in the prefrontal cortex of SHR as well as reduce the hyperactivity and attention deficit behavior in SHR, while the opposite was true for the GR inhibitor. It is suggested that the dysfunction of the 5-HT system in ADHD rats is closely related to glucocorticoid receptor activity.